PTMC IN PATIENTS WITH HIGH WILKIN’S SCORE - ALI , N; IRFAN, M; KHALID, MS (Biological and Clinical Sciences Research Journal, 2024)
Valvular mitral stenosis is a common problem in Pakistan and other countries of the subcontinent. Severe symptomatic mitral stenosis requires either the replacement of the mitral valve surgically or by Percutaneous Transluminal Mitral Commissurotomy (PTMC). If the mitral valve is suitable anatomically that is with a low Wilkin's score then PTMC being less invasive is considered to be a more preferred option. Objective: This Study is conducted to determine the success rate of PTMC in patients having high Wilkin’s scores. Methods: A total number of 94 patients with mitral stenosis planned for PTMC were included. Data regarding baseline patient characteristics such as age, gender, mitral valve area (MVA), Wilkin’s score, transmitral valve pressure gradients, and status of mitral regurgitation were collected. Patients with high Wilkin's score and high surgical risk undergoing PTMC were assessed by echocardiography after PTMC to determine its success as MVA >1.5 cm2 and up to 50% decrease in transmitral valve pressure gradients and no worsening of MR by no more than one grade. Results: The mean age of patients included in this study was 44.40±14.19 years. Mean pre-operative MVPG of patients was 29.17±4.41 and post-operative MVPG was 7.55±3.74. The mean pre-operative MVA of patients was 0.73±0.10 cm2 and the mean post-operative MVA was 1.78±0.40 cm2. There were 62 (65.96%) female and 32 (34.04%) male patients. The success of PTMC was achieved in 74 (78.72%). Conclusion: In the present study, we found a success rate of 78.7% in patients with a high Wilkins score of > 8. The procedure in this group of patients has an acceptable complication rate.